Updated inventory and ecological impacts of non-native fish in the Caspian Sea Basin: a systematic review of historical invasion pathways - Azad Teimori; Hamid Reza Esmaeili; Boris Levin; Keyvan Abbasi; Ekaterina D. Vasil’eva (Hydrobiologia, 2026)

DNA barcoding resolves the identity and invasion pathway of the non-indigenous goby genus Rhinogobius (Gobiiformes: Oxudercidae) in the Caspian Sea basin, and reveals cryptic diversity within the native range - Azad Teimori; Hamid Reza Esmaeili; Keyvan Abbasi; Fereshteh Pourhosseini; Mina Motamedi; Namiq Mustafayev; Boris A. Levin (Regional Studies in Marine Science, 2026)

Multivariate analysis and risk assessment associated with the consumption of carnivorous fish obtained from southwest Caspian Sea - Shima Bakhshalizadeh; Keyvan Abbasi; Rafael Mora-Medina; Nahúm Ayala-Soldado (Environmental Pollution, 2024)

Trophic transfer, bioaccumulation and translocation of microplastics in an international listed wetland on the Montreux record - Maryam Saemi-Komsari; Hamid Reza Esmaeili; Behnam Keshavarzi; Rosa Busquets; Keyvan Abbasi; Farideh Amini Birami; AmirHassan Masoumi (Environmental Research, 2024)

Characterization of ingested MPs and their relation with growth parameters of endemic and invasive fish from a coastal wetland - Maryam Saemi-Komsari; Hamid Reza Esmaeili; Behnam Keshavarzi; Keyvan Abbasi; Farideh Amini Birami; Mohammad Javad Nematollahi; Farhad Hosseini Tayefeh; Rosa Busquets (Science of The Total Environment, 2023)

Phylogeography and population structure of Ponticola gorlap (Teleostei: Gobiidae) in an evolutionary distinctive and ecologically threatened Caspian Sea sub-basin - Fatah Zarei; Hamid Reza Esmaeili; Reza Sadeghi; Bettina Reichenbacher; Ulrich K. Schliewen; Keyvan Abbasi; Ali Gholamhosseini (Aquatic Sciences, 2023)

Morphometric Analyses of Phenotypic Plasticity in Habitat Use in Two Caspian Sea Mullets - Shima Bakhshalizadeh; Keyvan Abbasi; Adeleh Rostamzadeh Liafuie; Ali Bani; Anu Pavithran; Francesco Tiralongo (Journal of Marine Science and Engineering, 2022)
To understand the functional meaning of morphological traits in the exploitation of natural resources, it is necessary to develop a quantitative, meaningful scheme for understanding ecophenotypes; this will facilitate management and conservation, which are the most pressing challenges in vulnerable aquatic environments. In this context, the management of cryptic and very similar species is more challenging, because of the difficulty of distinguishing them and determining their frequency in sympatry, even though they do not necessarily have the same ecologies. As such, in order to understand how morphological similarities are associated with their ecology, thirteen morphometric characteristics related to body landmark-based geometric morphometries, sagittal otolith morphology, and shape were examined in mature Chelon auratus and Chelon saliens, which were collected from the coastal waters of the southwest Caspian Sea between October 2020 and April 2021. Univariate and multivariate analysis of variance were conducted to evaluate the potential morphological differences between the species. The analyses highlight the morphological differences between C. auratus and C. saliens, and identify potentially helpful traits for using body and otolith shape for the interspecific distinction of these very similar species of Caspian mullet, which can reflect functional similarity and are an important component of community ecology.

Mitochondrial phylogeny, diversity, and ichthyogeography of gobies (Teleostei: Gobiidae) from the oldest and deepest Caspian sub-basin and tracing source and spread pattern of an introduced Rhinogobius species at the tricontinental crossroad - Fatah Zarei; Hamid Reza Esmaeili; Ulrich K. Schliewen; Keyvan Abbasi; Golnaz Sayyadzadeh (Hydrobiologia, 2021)

Genealogical concordance, comparative species delimitation, and the specific status of the Caspian pipefish Syngnathus caspius (Teleostei: Syngnathidae) - Fatah Zarei; Hamid Reza Esmaeili; Keyvan Abbasi; Golnaz Sayyadzadeh; Soheil Eagderi; Brian W. Coad (Marine Ecology, 2021)
To evaluate the specific validity of the Caspian pipefish Syngnathus caspius , we used a comparative molecular species delimitation method on a COI barcode library of Syngnathus , as well as principles of genealogical concordance. Comparative species delimitation allowed us to delineate putative species without a priori assignment of individuals to nominal species, while genealogical concordance extended our species delimitation results to multiple genes, multiple codistributed species, and comparisons with biogeographic evidence. All species delimitation analyses including two topology‐based, one network‐based, and one distance‐based analysis showed genetically isolated lineages of pipefish in the Black and Caspian Sea, corresponding to S. abaster and S. caspius , respectively. Mean evolutionary divergence between the two lineages (0.029) was within the range separating species of Syngnathus (0.024–0.217). The interclade/intraclade ratio of variation was comparable to the operational criterion of divergence between clades greater or equal to 10 × the level within clades to recognize separate species. Our argument on taxonomic validity of S. caspius is also supported by the principles of genealogical concordance as a conceptual basis for recognition of biological species. As a second objective, using a limited number of S. caspius specimens from two semi‐confined water bodies along the Caspian Sea south coastal zone (i.e., Anzali Wetland in the west and Gorgan Bay in the east), we searched for a possible matrilineal structure. The retrieved phylogeographic pattern was characterized by a shallow genealogy and lineage distributions varied, most probably caused by low to modest contemporary gene flow between populations of S. caspius across the southern Caspian Sea that are linked tightly through history.

Diet Survey and Trophic Position of Macrobrachium nipponense in the Food Web of Anzali Wetland - Alireza Mirzajani; Ahmad Ghane; Siamak Bagheri; Keyvan Abbasi; Mostafa Sayadrahim; Morteza Salahi; Fatemeh Lavajoo (Wetlands, 2020)